Optical coherence tomography angiography as a surrogate marker for end-organ resuscitation in sepsis: A review - Courtie, Ella; Gilani, Ahmed; Veenith, Tonny; Blanch, Richard J. (Frontiers in Medicine, 2022)
Sepsis is a severe illness which results in alterations in the end organ microvascular haemodynamics and is associated with a high risk of mortality. There is currently no real-time method of monitoring microcirculatory perfusion during sepsis. Retinal microcirculation is closely linked to cerebral perfusion and may reflect systemic vascular alterations. Retinal perfusion can be assessed using the non-invasive imaging technique of optical coherence tomography angiography (OCTA). This narrative review aims to discuss the utility of using retinal imaging and OCTA in systemic illness and sepsis. OCTA can be used as a functional, non-invasive and real-time biomarker along with other haemodynamic parameters for assessing and managing patients with sepsis.